Characterising Twitter Reply Chains in the Australian Twittersphere - Moon, Brenda (AoIR Selected Papers of Internet Research, 2017)
This research contributes to the understanding of conversation on Twitter by looking at reply chain networks in the Australian Twittersphere. By examining all of the reply chains in November 2016 from the comprehensive TrISMA dataset this paper develops a description of the characteristics of reply chains in the Australian Twittersphere. This approach advances beyond the limitation to specific pre-identified topics as expressed through keywords and hashtags, and builds on the author’s previous work in developing methods to trace conversations both backwards and forwards from selected seed tweets. This results in a considerably more complete picture of Twitter conversations than has been developed in the past. Reply chains features such as the number of tweets in the chain, duration of the conversation, the interval between tweets, branching structure, and number of participating accounts, as well as tweet content features such as links, topics, and images are examined to identify characteristics which can be used to classify the reply chains. I will present an analysis of these different metrics for reply chains in the Australian Twittersphere and evaluate their utility in categorising their different conversational patterns. This may make it possible to computationally distinguish single-authored threads, rapid and heated arguments, extended chats, multi-user responses to a single controversial tweet, and other types of conversation. This has important applications in large-scale, automated social media discourse analysis and in the computational filtering of ‘big social data’ into smaller samples for manual analysis.